2009 35th Annual Conference of IEEE Industrial Electronics 2009
DOI: 10.1109/iecon.2009.5415385
|View full text |Cite
|
Sign up to set email alerts
|

A model predictive control scheme with torque ripple mitigation for permanent magnet motors

Abstract: This paper presents a scheme that allows both to determine speed and rotor position of permanent magnet synchronous motors and to identify their inherent torque ripple. A model predictive control algorithm is proposed to control the torque with a high dynamic performance and to simultaneously eliminate the identified torque harmonics. The proposed concepts are validated experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[34] and [36], the authors present a multilevel six phase predictive controller where the number of inputs are reduced from 64 to the largest 12 vectors and a single zero vector in order to make the control law computationally fea sible. Other approaches for addressing this issue have been recently proposed including those that use explicitly solved offline controllers [32,37] branch and bound search methods for discard ing suboptimal sequences [19] and those that impose limits on the number of transistors that are allowed to switch during each state transition [30]. In this paper, we extend our previous develop ments of a control Lyapunov (CLF) based approach that incorpo rates stability information in the input selection process [38].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[34] and [36], the authors present a multilevel six phase predictive controller where the number of inputs are reduced from 64 to the largest 12 vectors and a single zero vector in order to make the control law computationally fea sible. Other approaches for addressing this issue have been recently proposed including those that use explicitly solved offline controllers [32,37] branch and bound search methods for discard ing suboptimal sequences [19] and those that impose limits on the number of transistors that are allowed to switch during each state transition [30]. In this paper, we extend our previous develop ments of a control Lyapunov (CLF) based approach that incorpo rates stability information in the input selection process [38].…”
Section: Introductionmentioning
confidence: 93%
“…The resulting con trol method, sometimes referred to as finite control set MPC (FCS-MPC), has recently lead to numerous efforts from within the DTC community mostly aimed at reducing switching fre quency [27][28][29][30][31] though other improvements have been achieved including the reduction of torque ripple [32][33][34], balancing capac itor voltages in multilevel inverters [20,28] and the inclusion of a modulator within the FCS-MPC framework to achieve a fixed switching frequency [35], While the adoption of FCS-MPC has greatly facilitated the use of predictive control techniques to power electronic systems, even the relatively small numbers of realizable actuator inputs can still present computational challenges when input sequences are eval uated over very small control periods. This has led some research ers to reduce the number of inputs considered in the optimization process.…”
Section: Introductionmentioning
confidence: 99%
“…5. It has been demonstrated that the PR controller implemented in stationary reference frame is the same as of PI regulators in rotating frame, these parameters can be tuned with the ‘technical optimum’ approach [16] using zero to cancel the pole as KPi=Lq4ξ2Td,Kii=KPiRLq,KRi=Kii where, Td=1.5Ts, ξ=0.8.…”
Section: Controller Designmentioning
confidence: 99%
“…A theoretical analysis of the offset-free properties of such an augmentation, within the MPC framework was performed [20]. An EMPC design for a current loop with estimation of the disturbances using the recursive least squares method fed forward for compensation was discussed [21]. An EMPC speed controller for an induction machine was designed considering load disturbance as an additional state variable, and a Kalman filter was applied to correct the predicted state variables to reject the disturbance [22].…”
Section: Introductionmentioning
confidence: 99%